Perbedaan Penerapan Whistleblowing System pada Perusahaan Perbankan di Indonesia - Dian Sasmita; Ainun Arizah; Nurhidayah Nurhidayah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Whistleblowing System (WBS) has become an important instrument in strengthening transparency, accountability, and fraud prevention within the banking sector. Variations in implementation quality among state-owned banks indicate that the effectiveness of WBS is influenced not only by the existence of reporting mechanisms but also by governance practices that support their operation. A qualitative approach with a comparative descriptive design was employed to examine the implementation of WBS in four Indonesian state-owned commercial banks: Bank Mandiri, BRI, BNI, and BTN. Secondary data were collected from annual reports, sustainability reports, corporate governance reports, and relevant regulatory documents published during 2022–2024. Data were analyzed using content analysis focusing on reporting channels, whistleblower protection, implementation independence, transparency, and follow-up mechanisms. Findings reveal that all banks have incorporated WBS as part of Good Corporate Governance practices; however, notable differences remain in implementation quality. BNI and BTN demonstrate stronger independence through third-party involvement, while Bank Mandiri shows the highest consistency in report resolution. BRI provides broader reporting access but faces challenges in maintaining reporting consistency. Effective WBS implementation is closely associated with organizational commitment, protection mechanisms, transparency of case handling, and stakeholder trust. These findings highlight that strengthening governance quality is essential for maximizing the contribution of WBS to fraud detection, organizational accountability, and sustainable corporate governance in the Indonesian banking industry.